Antidiabetic potential of karamunting leaves ethanolic extract as a natural herb: Blood glucose levels and pancreatic islets histomorphology on diabetic rats model - Ida Yuliana; Asnawati Asnawati; Maria Ulfah; Eko Suhartono (Faculty of Medicine, Universitas Islam Indonesia, 2021)
Background: Karamunting leaf is a wetland herb with antioxidant compounds that bind free radicals, reduce oxidative stress, reduce insulin resistance, and prevent the development of pancreatic cell dysfunction and damage.Objective: This study aims to prove the antidiabetic potential of the karamunting leaves ethanolic extract in treating diabetes in white male rats.Methods: This study used a true experimental with a pre-test and post-test control group design. Thirty rats were divided into four groups (control: C, ethanol extract of karamunting dose of 100 mg: P1, 200 mg: P2, and 400 mg: P3). Data on fasting blood glucose levels were taken before (pre-test) and after treatment (post-test). Data on pancreatic islets histomorphological changes (size, number, constituent cells) were analysed quantitatively. Fasting blood glucose levels were analysed using paired t-test, while the histomorphological data of the pancreatic islets were analysed using ANOVA. The data were considered significant if the p-value <0.05 (95% CI).Results: Karamunting leaf ethanol extract treatment reduced fasting blood glucose levels in diabetic rats. A 200 mg/kgBW was demonstrated as the most effective dose that improves the islets and cells number compiles the pancreatic islets, potentially treating diabetes mellitus (DM).Conclusion: Karamunting leaf ethanol extract potential as a natural herbal medicine in treating DM.